A comparison of technique survival in Canadian peritoneal dialysis and home hemodialysis patients. Issue 11 (6th May 2019) - Trinh, Emilie; Hanley, James A; Nadeau-Fredette, Annie-Claire; Perl, Jeffrey; Chan, Christopher T
Abstract: Background: High discontinuation rates remain a challenge for home hemodialysis (HHD) and peritoneal dialysis (PD). We compared technique failure risks among Canadian patients receiving HHD and PD. Methods: Using the Canadian Organ Replacement Register, we studied adult patients who initiated HHD or PD within 1 year of beginning dialysis between 2000 and 2012, with follow-up until 31 December 2013. Technique failure was defined as a transfer to any alternative modality for a period of ≥60 days. Technique survival between HHD and PD was compared using a Fine and Gray competing risk model. We also examined the time dependence of technique survival, the association of patient characteristics with technique failure and causes of technique failure. Results: Between 2000 and 2012, 15 314 patients were treated with a home dialysis modality within 1 year of dialysis initiation: 14 461 on PD and 853 on HHD. Crude technique failure rates were highest during the first year of therapy for both home modalities. During the entire period of follow-up, technique failure was lower with HHD compared with PD (adjusted hazard ratio = 0.79; 95% confidence interval 0.69–0.90). However, the relative technique failure risk was not proportional over time and the beneficial association with HHD was only apparent after the first year of dialysis. Comparisons also varied among subgroups and the superior technique survival associated with HHD relative to PD was less pronounced in more recent years and among older patients. Predictors of technique failure also differed between modalities. While obesity, smoking and small facility size were associated with higher technique failure in both PD and HHD, the association with age and gender differed. Furthermore, the majority of discontinuation occurred for medical reasons in PD (38%), while the majority of HHD patients experienced technique failure due to social reasons or inadequate resources (50%). Conclusions: In this Canadian study of home dialysis patients, HHD was associated with better technique survival compared with PD. However, patterns of technique failure differed significantly among these modalities. Strategies to improve patient retention across all home dialysis modalities are needed.